The All-on-four concept for fixed full-arch rehabilitation of the edentulous maxilla and mandible: a longitudinal study in Japanese patients with 3–17-year follow-up and analysis of risk factors for survival rate - Takashi Uesugi; Yoshiaki Shimoo; Motohiro Munakata; Daisuke Sato; Kikue Yamaguchi; Michiya Fujimaki; Kazuhisa Nakayama; Tae Watanabe; Paulo Malo (International Journal of Implant Dentistry, 2023)
Abstract Purpose Implant-supported immediately loaded fixed full-arch rehabilitation via All-on-four treatment yields good long-term results for both the maxilla and the mandible. However, the risk factors affecting long-term implant survival are unknown, and the long-term prognosis of All-on-four concept procedures in Japanese individuals has not been elucidated. We aimed to determine the cumulative implant survival rate after 3–17-year follow-up and identify the associated risk factors. Methods We analysed 561 cases (307 maxillae, 254 mandibles) with 2364 implants (1324 maxillae, 1040 mandibles) that received All-on-four treatment. We investigated the cumulative implant- and patient-level survival rates and various risk factors for implant failure. Statistical analysis was performed using the log-rank test for differences in Kaplan–Meier curves, univariate analysis using the Chi-square test, and multivariate analysis for risk factors affecting the survival rate. Results The cumulative survival rate was 94.4% by patient level and 97.4% by implant level for the maxilla, and 96.7% by patient level and 98.9% by implant for the mandible, with up to 17 years of follow-up. The maxillary survival rate at the implant level was significantly lower (p < 0.05). Furthermore, the maxillary survival rate within 24 months was significantly lower at the implant level (p < 0.01). Multivariate analysis revealed that the maxilla was the most significant risk factor (p < 0.01). Conclusions All-on-four treatment yielded high long-term survival rates in Japanese patients. However, the maxilla showed a significantly lower cumulative survival rate than the mandible, while early failure was significantly higher. Furthermore, the maxilla was a significant risk factor influencing the survival rate.